Beltrão, lambadão, interactivity and decolonialidade: Possible dialogues (Revista Internacional de Folkcomunicação, 2018)
The present article arose from restlessnesses raised in the Graduate Program in Contemporary Culture Studies of the Federal University of Mato Grosso, which has the decoloniais and folkcomunicacional theories among some of its guiding axes. The object of analysis is the video "Concurso de Lambadão", produced by the subject-author K-Bça Pensante, from his rereading of the dance sequence of “Pulp Fiction” (TARANTINO, 1994). The interactivity presents in the movie is the ingredient used by K-Bça to composit the new audiovisual text. In narrating all the activities that compose the night of cuiabana's lowland, the subject-author interacts with the original Pulp Fiction scene, which there is also a dance competition, contributing to the strengthening of the cuiabana culture, that, in a Beltranian characterization, is reaffirmed in combating the implantation of a planetary identity, in a decolonial movement. Interactivity; Lambadão; Folkcommunication; Decoloniality; Culture.